HUBUNGAN PEMBELAJARAN SENAM KREASI TERHADAP MINAT BELAJAR SENAM SISWA SMA TAMAN SISWA PADANG - Dina Anggraini; Romi Mardela; Padli; Anisa Sholiha Mia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between creative gymnastics learning and the interest in learning gymnastics among students at Taman Siswa High School, Padang. Creative gymnastics learning is an innovation in physical education that combines movement variations, creativity, musical rhythm, and active student involvement, creating a more engaging and enjoyable learning environment. Learning interest is a crucial factor influencing student engagement in the learning process. Therefore, a learning model that can enhance student interest in gymnastics material is needed. This study used a quantitative method with a correlational research method. The study population consisted of 14 students at Taman Siswa High School, Padang, and the entire population was sampled using a total sampling technique. The research instrument used a creative gymnastics learning questionnaire and a gymnastics learning interest questionnaire. Data analysis was performed using descriptive statistics, the Shapiro-Wilk normality test, the linearity test, and the Pearson Product Moment correlation test using SPSS version 27. The results showed a correlation coefficient of 0.913 with a significance value of 0.000 (<0.05). These findings indicate a significant relationship between creative gymnastics learning and students' interest in learning gymnastics. The better the implementation of creative gymnastics learning, the higher the interest in learning gymnastics among students at Taman Siswa High School, Padang.